Coopting the Antiviolence Movement: Why Expanding DNA Surveillance Won't Make Us Safer - SaIIomi, Megan (Social justice, 2012)
Expanding the number of individuals with DNA "profiles" stored in nationwide criminal databanks appears to be a promising criminal justice reform, particularly for resolving crimes of sexual violence. Bills like the Violence Against Women Act provide for DNA databank expansion, and many anti-rape organizations support this development. Yet, as millions of dollars are allocated for these purposes, thousands of rape kits-DNA evidence submitted by rape survivors-remain untested. DNA databanks have serious, harmful consequences for individual privacy and dignity, and they distract attention and resources from the larger social forces that engender sexual violence. Instead, the author advocates for community-based alternatives that are survivor-centered and focused on humanizing and healing all parties involved.